Enhancing English as a Foreign Language (EFL) Learners’ Writing with ChatGPT: A University-Level Course Design - Tseng, Yu-Ching; Lin, Yi-Hsuan (Electronic journal of e-Learning, 2024)
This research explores the innovative integration of OpenAI’s GPT-3.5 within a university-level English as a Foreign Language (EFL) writing course, illustrating a novel approach to academic instruction. The course follows the ADDIE instructional design model, encompassing five systematic stages: analysis, design, development, implementation, and evaluation. This model serves as the backbone of the course structure, ensuring a comprehensive educational experience. The incorporation of the Technological Pedagogical Content Knowledge (TPACK) framework in this course facilitates the effective integration of GPT-3.5 by enabling instructors to align advanced AI capabilities with appropriate pedagogical strategies, thereby enhancing the learning experience. TPACK guides educators in applying GPT-3.5’s features in a manner that is contextually relevant and pedagogically sound, ensuring the technology’s use complements the course content. The findings from this research are significant. They reveal that GPT-3.5 addresses three fundamental challenges often encountered in academic writing courses. Firstly, it enhances efficiency by providing immediate feedback and generating content ideas, accelerating the writing process. Secondly, GPT-3.5 ensures cohesive organization within students’ writing, guiding them to structure their thoughts more logically. Lastly, it serves as a reliable substitute for traditional peer reviewers, offering critical and objective feedback that students can use to refine their drafts. As students engage with AI, they enter a dynamic partnership. This collaboration with GPT-3.5 fosters critical thinking and empowers students to develop a distinctive writing voice. Through this interaction, students are not merely passive recipients of knowledge but active participants in a learning process that is augmented by cutting-edge technology. This study not only provides insight into the potential of AI-augmented academic writing but also highlights GPT-3.5’s role in promoting writing proficiency. It demonstrates that the application of AI in education can enhance the learning experience without compromising the individuality of student expression.